Effect of Tea Tree, Thymus Vulgaris and Nigella Sativa Oils on The Elimination of Enterococcus Faecalis (In Vitro Study) - Rafid J. Al-Badr; Hussain F. Al-Huwaizi (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: The main goal of chemomechanical endodontic treatment is the reduction or elimination of microorganisms from root canal system. The intracanal medicaments were used to enhance the disinfection process. This study was conducted to evaluate the antibacterial effect of thymus vulgaris, tea tree essential oils and cold pressed black seed oil (BSO) against E.faecalis. Materials and methods: E.faecalis was isolated from ten patients in need for endodontic treatment. The sensitivity of E.faecalis to the tested oils was evaluated in different concentrations in agar well diffusion method and compared with calcium hydroxide. The sensitivity of E.faecalis to vapor of the tested oils was also evaluated, in disk vaporization method using inverted agar plate and compared to tricresol formalin (TC) and camphorated monochlorophenol (CMCP). The micro broth dilution method was used to evaluate the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the tested oils against E.faecalis. The presence of biologically active volatile components of two samples of BSO with different origins was evaluated by the use of high performance liquid chromatography (HPLC). Results: All the tested oils exhibited antibacterial activity against E.faecalis in different concentrations with different levels in agar well diffusion and disk vaporization methods. The MBC was 2µl/mL, for thymus vulgaris oil and 32µl/mL for tea tree and Black seed oils. The vapor forming medicaments (TC and CMCP) induced effective antibacterial action but calcium hydroxide showed a low antibacterial action against E.faecalis. The active volatile components were present in one sample of BSO only (the Iraqi one). Conclusion:The three oil extracts were active against E.faecalis, and the origin, condition of storage and method of extraction may affect the components of cold pressed black seed oil.